A Randomized Trial of Time-Limited Antiretroviral Therapy in Acute/Early HIV Infection. - Joseph B Margolick; Linda Apuzzo; Joel Singer; Hubert Wong; Terry Lee; Joel E Gallant; Phillippe El-Helou; Mona R Loutfy; Anita Rachlis; Christopher Fraser; Kenneth Kasper; Cécile Tremblay; et al. (PLoS ONE)
Background It has been proposed that initiation of antiretroviral treatment (ART) very soon after establishment of HIV infection may be beneficial by improving host control of HIV replication and delaying disease progression. Methods People with documented HIV infection of less than 12 months' duration in Baltimore MD and seven Canadian sites were randomized to either a) observation and deferred ART, or b) immediate treatment with ART for 12 months. All subjects not receiving ART were followed quarterly and permanent ART was initiated according to contemporaneous treatment guidelines. The endpoint of the trial was total ART-free time from study entry until initiation of permanent ART. Results One hundred thirteen people were randomized, 56 to the observation arm and 57 to the immediate treatment arm. Twenty-three had acute (<2 months) infection and 90 early (2-12 months) infection. Of those randomized to the immediate treatment arm, 37 completed 12 months of ART according to protocol, 9 declined to stop ART after 12 months, and 11 were nonadherent to the protocol or lost to follow-up. Comparing those in the observation arm to either those who completed 12 months of ART or all 56 who were randomized to immediate ART, there was no significant difference between the arms in treatment-free interval after study entry, which was about 18 months in both arms. Conclusions This study did not find a benefit from administration of a brief, time-limited (12-month) course of ART in acute or early HIV infection. Trial registration ClinicalTrials.gov NCT00106171.